Exit strategy [compact disc, unabridged] : a Nick Mason novel - Hamilton, Steve, 1961- (Hamilton, Steve, 1961- Nick Mason novel., 2017)
Nick Mason has been given a true mission impossible: Infiltrate WITSEC, the top-secret federal witness-protection program that has never been compromised, locate the three men who put his boss Darius Cole behind bars for life, and kill them. As he risks everything to complete his mission, Mason finds himself being hunted by the very man he replaced, the ruthless assassin who once served, then betrayed, Darius Cole. Rather than waiting to be Mason's next victim, he has escaped witness protection to hunt down and kill Mason himself.